The Effect of Hemorrhage Volume on Mortality in Spontaneous Intracerebral Hemorrhages - İsmail Erkan Aydın; Çağdaş Yıldırım; Şeyda Tuba Savrun; Atakan Savrun; Alp Şener (Van Tıp Dergisi, 2021)
INTRODUCTION: Spontaneous intracerebral hemorrhage is associated with severe morbidity and mortality. In this study, it was aimed to investigate the effect of hemorrhage volume and other known prognostic factors on mortality in spontaneous intracerebral hemorrhages. METHODS: The study was performed retrospectively in patients diagnosed with spontaneous intracerebral hemorrhage at a state hospital emergency department between 01/01/2014- 31/12/2019. Ethical approval was obtained from the Local Clinical Research Ethics Committee for the study. Patients' age, gender, systemic disease, antiaggregant or anticoagulant medication use, systolic blood pressure (SBP) and Glasgow Coma Scale (GCS), INR, hemorrhage volume, ventricular extension of hemorrhage and location determined by computed tomography (CT), ICH (Intracerebral Hemorrhage) Score, 30-day mortality data were retrospectively assessed for the study. RESULTS: A total of 55 patients, 26 males (47.27%), 29 females (52.73%) were included in the study. The mean age was detected as 70 +- 13. The 30-day mortality rate was 49.09%. Mortality was significantly higher in patients with ventricular extension of hemorrhage (p <0.001). When subgroup analysis was done, in the group with mortality in supratentorial hemorrhages, the volume of hemorrhage was significantly higher (p <0.001). A moderate to high degree of negative correlation was found between GCS and hemorrhage volume (p <0.001; rho = -0.599). When multivariate analysis of factors predicting mortality was performed, only GCS had an effect on mortality. DISCUSSION AND CONCLUSION: Hemorrhage volume is associated with increased mortality in spontaneous intracerebral supratentorial hemorrhages. Lower GCS on admission was associated with mortality in our retrospective cohort study.